Development of the Learning Process of Ancient Pali Grammar Scriptures through Online System - Thumthong, Supee; Paññādīpo, Phramaha Wattana; Suwanprathip, Thanee (Journal of Dhamma for Life, 2025)
This research is a documentary study with the following objectives: 1) to examine the current state of learning management for ancient Pali grammar texts,2) to translate the Padarupasiddhi and Abhidhanappadipika texts and explore online learning management methods, and 3) to develop an online learning process for ancient Pali grammar texts. The research findings reveal that ancient Pali grammar texts contain intricate content requiring extensive study time and are not included in the current Pali Pariyatti education system. Presently, the teaching and learning of these ancient texts are mostly conducted informally by private initiatives. The translation of the Padarupasiddhi (Sandhikanda) in a literal manner clarifies the rules of Pali grammar and provides an understanding of how to construct Pali word forms using the Kaccayana grammatical formulas. The Abhidhanappadipika (Pali translation) introduces a vast number of Pali words, including synonyms (e.g., 32 words meaning "Buddha") and polysemous words (e.g., the word "samaya" has nine meanings). Regarding the online learning process, knowledge is disseminated through platforms such as websites, Facebook, YouTube, and TikTok to align with modern trends and cater to learners' convenience. When teaching via Zoom, the majority of participants responded very positively. Additionally, the content was disseminated through various media: (1) a website for audio files and learning materials, (2) YouTube for full lecture videos and short example clips, (3) TikTok for short explanatory clips on the Abhidhanappadipika, and (4) printed books distributed as Dhamma donations.